2008
DOI: 10.1021/jp8060575
|View full text |Cite
|
Sign up to set email alerts
|

Free Volume Dependence of the Internal Rotation of a Molecular Rotor Probe in Room Temperature Ionic Liquids

Abstract: The fluorescence efficiency of a well-known microviscosity probe, 9-(dicyanovinyl)julolidine (DCVJ), which is highly sensitive to the viscosity of the medium, has been studied in seven imidazolium ionic liquids (ILs) of varying viscosities over a temperature range of 10-60 degrees C. The microviscosities around the probe in different ILs have been estimated from the linear dependence of the logarithm of fluorescence quantum yield (log phi(f)) on the logarithm of the bulk viscosity (log eta) in various conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 86 publications
(67 reference statements)
4
66
1
Order By: Relevance
“…Generally, greater viscosity will result in greater free volume dependence and a greater value of x. [45,59] In [BmPr][NTf 2 ], at both excitation wavelengths, the values of x are almost the same, so it is clear that, for both excitation wavelengths, the free volume experienced by the ThT dye are almost the same and it is expected that the microviscosity faced by ThT at these two excitation wavelengths are almost same. On the other hand, in [N 1888 ][NTf 2 ], the value of x when l exi = 405 nm is higher than that at l exi = 445 nm.…”
Section: Dependence Of Photophysics Of Tht On Viscosity and Temperaturementioning
confidence: 99%
“…Generally, greater viscosity will result in greater free volume dependence and a greater value of x. [45,59] In [BmPr][NTf 2 ], at both excitation wavelengths, the values of x are almost the same, so it is clear that, for both excitation wavelengths, the free volume experienced by the ThT dye are almost the same and it is expected that the microviscosity faced by ThT at these two excitation wavelengths are almost same. On the other hand, in [N 1888 ][NTf 2 ], the value of x when l exi = 405 nm is higher than that at l exi = 445 nm.…”
Section: Dependence Of Photophysics Of Tht On Viscosity and Temperaturementioning
confidence: 99%
“…These values are in good agreement with the expected literature values for molecular rotors. [24,25] We note here that due to the change in the refractive index of the medium with increasing glycerol content the radiative rate k r will increase according to the Strickler-Berg formula [68,69] [Eq. (16)] by a factor www.chemphyschem.org of 1.2 (for 100 % methanol [n = 1.332 at 22 8C] to 100 % glycerol [n = 1.474 at 22 8C] mixtures).…”
Section: Time-resolved Measurementsmentioning
confidence: 99%
“…[16,17] DCVJ and other malononitriles have been widely used to date, including studies in high-pressure environments, [18][19][20] microviscosity of phospholipid vesicles and micelles as a function of temperature, [21] interaction with proteins in blood plasma, [22] and pharmaceutical systems for microviscosity measurements. [23] DCVJ has also been used as a probe of microviscosity and free volume in phospholipid bilayers [24] and ionic liquids, [25][26][27] for the self-association of tubulin, [28] and the transformation of actin from its monomeric G-state to its polymeric Fstate. [29] It has also been shown that the emission spectrum of DCVJ is dependent on the concentration of the dye, [30] and spectral fluorescence measurements of DCVJ have been used to study liposomes as a function of temperature and cholesterol content.…”
Section: Introductionmentioning
confidence: 99%
“…42 Many specific features, such as the significant difference between the bulk viscosity and microviscosity, have been observed due to this heterogeneous nature in RTILs. 43 Recently, a growing number of studies focused on the investigation of the physicochemical properties of the mixtures of RTILs and conventional solvents because the fine-turning solvent property after adding conventional solvents may broaden the scope of the applications of the RTILs. 44−57 Many studies on the effects of water, alcohols, and other polar or nonpolar organics in RTILs were carried out.…”
Section: Introductionmentioning
confidence: 99%